Risky revamping: managing data efficiently. (February 2016) - Palmer, Adrian
Abstract : Deutsche Bank recently announced plans for a significant restructure, with the Wall Street favourite preparing to split its investment bank in two. One arm is set to focus on corporate and investment banking, and the other on sales and trading. As part of the major overhaul, both divisions have brought in new professionals, and are soon set to announce their new executive committees.